Preparing athletes and staff for the first "pandemic" Olympic Games - Cardinale, M. (The Journal of Sports Medicine and Physical Fitness, 2021)
Severe acute respiratory syndrome Coronavirus 2 (SARS-CoV-2) is the virus causing Coronavirus disease 2019 (COVID-19). Since the World Health Organization declared the outbreak of pandemic on March 11, 2020, cases have been increasing around the World with more than 3-million deaths recorded and a daily number of COVID-19 cases 20 times higher than when the Olympics were postponed, at the time of writing. Governments adopted various lockdown measures forcing isolation for many weeks/months depending on the evolution of the disease in each country. The rapid transmission of the disease forced the Tokyo 2020 Olympics to be postponed for one year. Travel restrictions, quarantine requirements and isolation have been the norm for many athletes in preparation for the Olympic Games. Also, due to the measures put in place to reduce the spread of the disease, sporting facilities have been closed and competitions cancelled forcing athletes and their staff to find alternative solutions to maintain performance and continue preparing for the Olympics. This unique challenge is affecting the whole World, and while vaccination programs start to be deployed, in a few months the world will see the first Olympic Games` edition during a pandemic. The aim of this special paper was to consider the various challenges posed by the COVID pandemic and to provide information for coaching support staff to improve the preparation for Tokyo Olympics as well as consider the possible performance implications of this unique Olympic edition.